Identification of the Need for the Development of Teaching Materials for Animalia Class X High School - Purwati Purwati; Etika Dyah Puspitasari (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2021)
Animalia is a biology subject that includes in Grade X Senior High School. This material has a comprehensive scope so that in classroom learning, teaching and learning activities are not sufficient to cover all the material. Identification of teaching materials is necessary so that the teaching materials developed are under the needs of teachers and students. The purpose of this research, to analyze the developing teaching materials needs on Animalia material at SMA Negeri 1 Srandakan. This type of research is a survey with a descriptive analysis method. The research population is the teachers and students of class XI. The sample was chosen by one biology teacher and students randomly as many as 30 people. This research used interviews and online questionnaires distributed through the WhatsApp application in collecting the data. The data analysis technique used is descriptive quantitative. The results showed that the problems faced by students in studying Animalia material included material that was too broad, memorized a lot, and was full of the use of Latin names. Students do not have textbooks or other handbooks in understanding Animalia material. The material presented on the internet is not fully understood. The teaching materials provided by the teacher have shortcomings, namely: the explanation is difficult to understand, the pictures served are incomplete, and less attractive. Meanwhile, the obstacles faced by the teacher were difficulties in completing the Animalia material due to limited time with too much material coverage. The teaching materials that need to be developed are handouts. Handout teaching materials can facilitate students as learning support for Animalia material which has a comprehensive scope and helps teachers deliver the material. This research is part of the research on developing digital handouts on Animalia material at SMA Negeri 1 Srandakan.